Pengaruh Motivasi, Lingkungan Kerja, Pelatihan dan Bornout Syndrome terhadap Kinerja Karyawan pada Perusahaan Manufaktur Otomotif di Jakarta Timur - Tosin, Muhamad; Susilastuti, Darwati; Astuty, Pudji; Helmi, Yuni (Universitas Mercu Buana, 2023)
This study examines which factors are most dominant that can affect employee performance, where these factors include Motivation, Work Environment, Training and Burnout Syndrome. This factor is used as an independent variable, and to predict its relationship or influence on employee performance, it is used as the dependent variable. The sampling technique used is Simple Random Sampling where the sample is taken randomly in the population where the sample obtained is 68 employees. To test the analysis of research instruments used validity test, reliability test and classical assumption test, while for statistical analysis test and analysis of relationships and influence used correlation test, coefficient of determination and multiple linear regression. The results showed that the Motivation Variable had a positive and significant influence on Employee Performance by 0.562 or 56.2%, Work Environment Variables had a positive and significant influence on Employee Performance by 0.228 or 22.8%, Training Variables had a positive and significant influence on Employee Performance is 0.140 or 14% and the Burnout Syndrome Variable has no effect on Employee Performance at PT. MTS with the results obtained at 0.001.